The Inhibitory Receptor GPR56 (Adgrg1) Is Specifically Expressed by Tissue-Resident Memory T Cells in Mice But Dispensable for Their Differentiation and Function In Vivo - Cheng-Chih Hsiao; Natasja A. M. Kragten; Xianhua Piao; Jörg Hamann; Klaas P. J. M. van Gisbergen (Cells, 2021)
Tissue-resident memory T (TRM) cells with potent antiviral and antibacterial functions protect the epithelial and mucosal surfaces of our bodies against infection with pathogens. The strong proinflammatory activities of TRM cells suggest requirement for expression of inhibitory molecules to restrain these memory T cells under steady state conditions. We previously identified the adhesion G protein-coupled receptor GPR56 as an inhibitory receptor of human cytotoxic lymphocytes that regulates their cytotoxic effector functions. Here, we explored the expression pattern, expression regulation, and function of GPR56 on pathogen-specific CD8+ T cells using two infection models. We observed that GPR56 is expressed on TRM cells during acute infection and is upregulated by the TRM cell-inducing cytokine TGF-β and the TRM cell-associated transcription factor Hobit. However, GPR56 appeared dispensable for CD8+ T-cell differentiation and function upon acute infection with LCMV as well as Listeria monocytogenes. Thus, TRM cells specifically acquire the inhibitory receptor GPR56, but the impact of this receptor on TRM cells after acute infection does not appear essential to regulate effector functions of TRM cells.